Non-monotonic approach to Robust H∞ control of multi-model systems. ([2019]) - Wen, Jiwei; (Professor of electrical; computer engineering), Nasiri, Alireza; Nguang, Sing Kiong; Almakhles, Dhafer J
No abstract available